Transmeta's magic show [microprocessor chips]. - Geppert, L. (IEEE spectrum)
It took Transmeta engineers 100 million dollars, five years of secret toil, and a little magic to create fast low-power chips that turn into x86s in a microsecond. Transmeta Corporation's Crusoe chips look nothing like Intel's Pentium processors. They do not even have a logic gate in common. They are smaller, consume between one-third and one-thirtieth the power (depending on the application), and implement none of the same instructions in hardware. However the Crusoe microprocessors can run the same software that runs on IBM PC-compatible personal computers with Pentium chips-for instance, Microsoft Windows or versions of Unix, along with their software applications. The paper describes the development of the Crusoe chips